Balancing Work Life: Job Crafting, Work Engagement, and Workaholism in the Finnish Public Sector - Nissinen, Terhi Susanna; Maksniemi, Erika Ilona; Rothmann, Sebastiaan; Lonka, Kirsti Maaria (Frontiers in Psychology, 2022)
The aim of this study was to investigate how job crafting, work engagement, and workaholism were related in public sector organizations. The participants (N = 213) were civil servants from three Finnish public organizations, representing different professions, such as school personnel, secretaries, directors, parking attendants, and ICT specialists. We duly operationalized job crafting, work engagement, and workaholism by using the Job Crafting Scale, the UWES-9, and the Work Addiction Risk Test. The current study focused on the Finnish public sector, since work engagement is recognized at the governmental level and has been shown to be strongly and positively associated with economic activity and productivity, while workaholism is associated with poor well-being. We analyzed the data by using structural equation modeling and found that three job crafting dimensions were strongly intertwined with one another. These dimensions were increasing structural job resources, increasing social job resources, and increasing challenging job demands. In the structural model, dimension “increasing structural job resources” was positively related to work engagement, whereas dimension “decreasing hindering job demands” was negatively associated with workaholism. This study highlighted the relevance of employees learning to balance their job resources and demands. We recommend that, in the public sector, employees be systematically encouraged to practice job crafting behavior by enabling them to increase structural job resources. These results are of high relevance, considering the heavy workload of public sector employees during the COVID-19 pandemic.